2016
DOI: 10.1097/sap.0000000000000545
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Free Flap Breast Reconstruction After Unilateral Radiation

Abstract: Intraoperative vascular complications and postoperative wound infections are significantly more likely to occur in autologous breast free flap reconstruction with previous radiation therapy. It is important to plan for and counsel patients that fields with previous radiation are at higher risk for these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 20 publications
1
27
1
1
Order By: Relevance
“…Intraoperative vascular complications and postoperative wound infections have been shown to be significantly more likely to occur in the setting of autologous free flap reconstruction after PMRT, and it is felt that the timing of reconstruction may play a role. 29 A study by Baumann et al demonstrated that patients who underwent reconstruction at a minimum of 12 months from completion of PMRT developed fewer complications, including microvascular thrombosis and total flap loss, than those who underwent delayed reconstruction within 12 months of completing therapy. 30 However, other studies reveal that patients who undergo autologous reconstruction within versus after 12 months following PMRT have no significant differences in complications.…”
Section: Resultsmentioning
confidence: 99%
“…Intraoperative vascular complications and postoperative wound infections have been shown to be significantly more likely to occur in the setting of autologous free flap reconstruction after PMRT, and it is felt that the timing of reconstruction may play a role. 29 A study by Baumann et al demonstrated that patients who underwent reconstruction at a minimum of 12 months from completion of PMRT developed fewer complications, including microvascular thrombosis and total flap loss, than those who underwent delayed reconstruction within 12 months of completing therapy. 30 However, other studies reveal that patients who undergo autologous reconstruction within versus after 12 months following PMRT have no significant differences in complications.…”
Section: Resultsmentioning
confidence: 99%
“…8,9,2838 With well documented concerns, the general consensus has been to approach immediate reconstruction in patients requiring PMRT with caution and delay flap reconstruction until after radiation therapy in order to optimize reconstructive results and decrease radiation-associated flap complications. 39 Over time, there has been a swell in the level of interest for immediate breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Although indications for breast reconstruction are many, the significant factors are whether the reconstruction is immediate or delayed, 16 17 bilateral or unilateral, 18 in a radiated field, 19 20 or if there is a presence of an open wound. Bilateral reconstruction impacts the volume of tissue necessary and may require alternate donors if adequate tissue is not present to reconstruct two breasts.…”
Section: Flap Selectionmentioning
confidence: 99%